Evolution of Interest Rate Policy in Algeria: (1970- June 2015) From Restriction to Liberalization - Chelghoume, Amirouche (Milev Journal of Research and Studies, 2017)
The research aims to evaluate the effectiveness of interest rate policy in Algeria during the period (1970- June 2015); we can distinguish between two periods, financial repression period (1970- 1989), which characterized by the widespread interference by the state in financial system, through administrative determination of interest rates at low levels, this policy was responsible for excessive monetary expansion, low financial savings and misallocation of resources. Authorities liberalized various interest rates, policy rate and retail rates (debtor and creditor), in the framework of the transition to market based economy (1990- June2015). The research found limited success of the interest rate policy liberalization in the activation of monetary policy and banking intermediation in Algeria.